2015
DOI: 10.1007/s12206-015-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

Pool boiling performance of lithium bromide solution on enhanced tubes

Abstract: In the present study, pool boiling heat transfer coefficients of LiBr solution were obtained for smooth, corrugated, floral and low fin tubes. Test range covered saturation pressure from 7.38 kPa to 101.3 kPa, LiBr concentration from 0% to 50%. Low fin tube yielded the highest heat transfer coefficient followed by floral, corrugated and smooth tube. The sequence was the same independent of saturation pressure or LiBr concentration. For the low fin tube, the heat transfer enhancement ratio ranged from 1.34 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The dimensions of the model used in the present research are shown in Figure1. The computational dimensions are considered as follows in order to compare the results obtained from the present numerical research with the previous experimental studies by Sim et al [16,18].…”
Section: Problem Statementmentioning
confidence: 99%
“…The dimensions of the model used in the present research are shown in Figure1. The computational dimensions are considered as follows in order to compare the results obtained from the present numerical research with the previous experimental studies by Sim et al [16,18].…”
Section: Problem Statementmentioning
confidence: 99%
“…In absorption heat pumps, desorption is the separation process of the refrigerant fluid from the working mixture (integrated by a refrigerant fluid and an absorbent), and the component where the process takes place is called “desorber” (also known as generator). The most used desorber configurations are: Nucleate pool-boiling [ 19 , 20 , 21 , 22 , 23 , 24 ] and falling-film [ 25 , 26 , 27 , 28 , 29 ]. In the nucleate pool-boiling configuration, a constant heat load must be added in order to reach the working mixture saturation temperature to separate a part of the refrigerant fluid in the vapor phase.…”
Section: Membrane-based Desorbersmentioning
confidence: 99%